(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Severe traumatic brain injury can be a serious condition. Objective: The purpose of the present study was to see the decompressive craniectomy (DC) of severe traumatic brain injury. Methodology: This clinical trial was conducted in the Department of Neurosurgery at Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2012 to December 2013 for a period of two (02) years. Patients with the age of 18 years and above, GCS of the patients 8 to 4, severe traumatic brain injury (TBI) with multiple hemorrhagic contusions and midline shift, on CT scan and severe TBI with gradual neurological deterioration were included for this study. Total 60 patients were included. Result: A total of 60 patients were included in this study. Almost two third 18 (60.0%) patients had favorable outcome (GOS 4 and 5) in group A and exactly two third 20(66.7%) patients had Unfavorable outcome (GOS 1,2 and 3) in group B (p<0.05). In this study 8 patient died among which 5 had GCS 4 and 3 had GCS 5. One patient with GCS 5 became persistent vegetative. Eight patient with good recovery had GCS 8, 7 and 6. Death occurred at mean GCS 9±2.mm of midline shift followed by 8± mm in persistent vegetative, 5.67±2.08 mm in severe disability, 4.5±2.88 mm in moderate disability and 3.38±1.06 mm in good recovery. Conclusion: Group A had better clinical outcome than group B. So based on statistical analysis it can be concluded that DC is preferable to conservative management in case of severe TBI. Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 124-128